0004 Sleep Disruption By Chemo-genetic Activation Of Corticotropin Releasing Factor neurons In The Hypothalamic Paraventricular Nucleus Of Mice. (12th April 2019) - Kumar, Sunil; Hsieh, Kung-Chiao; Gvilia, Irma; Kolli, Chandra; McGinty, Dennis; Szymusiak, Ronald
Abstract: Introduction: Activation of corticotropin releasing factor (CRF) neurons in the paraventricular nucleus of the hypothalamus (PVN) regulates endocrine and behavioral responses to acute stress. We hypothesized that selective activation of CRF neurons in the PVN acutely disturbs sleep. We examined the effects of chemo-genetic activation of CRF neurons in the PVN on spontaneous sleep-wake and EEG measures in mice. Methods: 6 male CRF-ires-Cre mice received bilateral injections of pAAV-hSyn-DIO-hM3D(Gq)-mCherry (excitatory DREADD) and 3 mice received pAAV-hSyn-DIO-mCherry (control vector) targeting the PVN. Mice were also implanted with EEG/EMG electrodes. Mice were maintained 12/12 hr light dark cycle. Three weeks after AAV injections, intraperitoneal injections of vehicle or CNO (0.1 mg/kg), were administered at zeitgeiber time (ZT) 0 in a repeated measure experiments. EEG and EMG were recorded undisturbed post-injection. EEG slow-wave activity (SWA) in NREM sleep (% change from baseline values) and sleep wake measures were quantified during 8 hour post-injection. Results: During first 4-hr post-injection in mice expressing excitatory DREADD, percent time awake increased following 0.1 mg/kg CNO compared to vehicle (42.5±7.1%/75.0±10.7%, p=0.001) whereas NREM time (51.7±6.5%/24.1±3.8%, p=0.001) and REM time (5.7±0.05%/0.1±0.05%, p=0.001) decreased. In mice expressing control vector, these wake-sleep measures did not differ between 0.1 mg/kg CNO and vehicle injections. In the second 4-hr post-injection period, wake time (41.1±1.4%/39.1±2.5%, p=0.524), NREM time (50.9±0.8%/53.0±4.1%, p=0.646) and REM time (7.9±1.1%/7.9±1.9%, p=0.993) did not differ between and CNO and vehicle conditions. EEG slow-wave activity (SWA) in NREM sleep in first 4-hrs post-injection in mice expressing excitatory DREADD showed a significant decrease of 44%. Wake bout duration increased and NREM bout duration was decreased in first 4 hrs following CNO injection in mice expressing excitatory DREADD. There were no between treatment differences in REM bout duration. Conclusion: Acute activation of CRF neurons in the hypothalamic PVN acutely suppresses sleep. Support (If Any): By the Department of Veterans Affairs.